The Effect of Obstetric Complications (Premature Rupture of Membrans, Pre Eclampsia and Post Date) on the Type of Labor in Mojokasri Hospital - Sugiati Sugiati; Nurwijayanti Nurwijayanti; Nurdina Nurdina (Journal for Quality in Public Health, 2019)
Obstetric complications are complications that occur during the pregnancy process or complications that can occur after the mother gives birth, for example, KPD, Bleeding, Abortion, post date, Preeclampsia and Eclampsia and others that can cause risks to the mother and fetus that will affect labor (. The purpose of this study was to determine the effect of obstetric complications (KPD, Pre-eclampsia and Post Date) on the type of labor in Mojokasri Kawaananan, Mojokerto Regency in 2018. The design used in the study is Comparative. Population were all maternal obstetric complications (KPD, Pre Eklampsi, Post Date) in Mojokasri Hospital in June to August 2018 with a total of 186 people. The sample size is 126 respondents, using the simple random technique. Independent variables are Obstetric Complications (KPD, PEB and Post Date) the dependent variable is Type of Labor (Normal, Action, Sectio Caesarea). Data was collected using observation sheets, then analyzed using the Logistic Regression test. Statistical test results obtained from Kebidanan Complications obtained p value of 0,000 <α = 0.05, so that H0 is rejected and H1 is accepted. This means that the variable midwifery complication affects the type of labor Actions / sectio caesarea in Kawedanan Mojokasri, Mojokerto Regency